Knowledge, Attitude and Practice of Gynecologists at Public Teaching Hospitals in Sana'a City Towards Cervical Cancer Screening, -Yemen, 2020 - Al-Haddad , Kawkab Mohammed; Ba-Break, Maryam; Al-Jamrah , Khaled; Al Amad, Mohammed (International Journal For Research In Health Sciences And Nursing, 2021)
Background: Cervical cancer is the fourth most prevalent cancer among women causing 250, 0000 annual deaths worldwide. The available data, although limited, indicates that 8.5 million Yemeni women are at risk of developing cervical cancer and most cases are diagnosed at late stages causing deaths from this illness which could be prevented through screening. There is limited evidence about the awareness of health staff in Yemen about the importance, eligibility criteria, role and availability of cervical cancer screening as well as their attitude toward it and their utilization of this service either for themselves or their patients. The aim: To assess the knowledge, attitude, and practice (KAP) of gynecologists toward cervical cancer screening as well as barriers of implementing this screening service in Yemen. Methods: All physicians who provide gynecology and obstetrics care at the four main public teaching hospitals in Sana’a city were targeted in this cross-sectional study. The data was collected using a validated self-administered questionnaire. Findings: Gynecologists in the main public teaching hospitals in the capital of Yemen have a satisfactory knowledge of importance of screening of cervical cancer and positive attitude toward this service. However, their awareness and positive attitude are not well-reflected in the utilization of cervical cancer services, either for themselves or their patients. Barriers of using cervical cancer services include unawareness and misconceptions of gynecologists. Conclusion: The identified gap in gynecologists’ KAP and barriers should be addressed to enhance the neglected cervical cancer screening in Yemen toward better control of this serious preventable disease.